THE ROLE Of THE MICROBIOTA IN THE HUMAN BODY AND ITS IMPACT ON THE IMMUNE SYSTEM (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The role of the microbiota in the human body and its impact on the immune system has become a significant focus of scientific research in recent years. The microbiota, a complex ecosystem consisting primarily of bacteria, viruses, fungi, and other microorganisms, plays an essential role in various biological processes such as immune function, digestion, metabolism, and mental health.